2017
DOI: 10.3390/ijerph14091013
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Effective Municipal Solid Waste Management in a Rapidly Urbanizing Area in Thailand

Abstract: This study focused on determining the barriers to effective municipal solid waste management (MSWM) in a rapidly urbanizing area in Thailand. The Tha Khon Yang Subdistrict Municipality is a representative example of many local governments in Thailand that have been facing MSWM issues. In-depth interviews with individuals and focus groups were conducted with key informants including the municipality staff, residents, and external organizations. The major influences affecting waste management were categorized in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
85
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(108 citation statements)
references
References 30 publications
4
85
0
5
Order By: Relevance
“…Welfens et al [66] reported that knowledge is one of the significant key drivers of waste separation and disposal behaviors. There are several other studies underlining the significance of awareness on the effective implementation of HSW on the local level [49,[67][68][69]. On the contrary, Chen et al [15] and Zhang et al [47] have reported that a high awareness and knowledge on HSW management does not necessarily translate into action.…”
Section: The Overall Feedback and Motivation/demotivation Factorsmentioning
confidence: 99%
“…Welfens et al [66] reported that knowledge is one of the significant key drivers of waste separation and disposal behaviors. There are several other studies underlining the significance of awareness on the effective implementation of HSW on the local level [49,[67][68][69]. On the contrary, Chen et al [15] and Zhang et al [47] have reported that a high awareness and knowledge on HSW management does not necessarily translate into action.…”
Section: The Overall Feedback and Motivation/demotivation Factorsmentioning
confidence: 99%
“…Finally, as in most developing countries [15,116,117], the cost of waste collection and disposal is not covered through the revenues from collection fees, but from municipality funds budget and other sources. In this sense, the new ISWM law includes the possibility to use funds from the fossil fuel industry revenues for solid waste management activities (personal comm: I2; C3) (personal comm: C3; C1; C7; I2; I1).…”
Section: Sustainability Transitions In Bolivian Municipal Solid Wastementioning
confidence: 99%
“…Environment‐related studies (e.g., Asibor & Oghenekohwiroro, ; Binafeigha & Enwin, ; Estrellan & Iino, ; Guerrero, Maas, & Hogland, ; Gullett, Lemieux, Lutes, Winterrowd, & Winters, ; Papargyroponlon, Colenbrander, Sudamant, Gouldson, & Tin, ; Thompson, ; Yukalang, Clarke, & Ross, ; Ziraba, Haregu, & Mberu, ) have spelled out the biological and chemical reactions of solid waste and the corresponding effects when it is indiscriminately disposed of in the environment without required treatment. Environmental health problems resulting from such practices could be direct or indirect.…”
Section: Literature Reviewmentioning
confidence: 99%